Pretreatment of empty fruit bunch fiber: Its effect as a reinforcing material in composite panels - Chin, Kit Ling; Lee, Chuan Li; H’ng, Paik San; Mohamed Asa’ari, Ainun Zuriyati (Elsevier, 2022)
One of the lignocellulosic wastes that has obtained much interest in Malaysia is oil palm empty fruit bunch (EFB). EFB is sustainable and renewable as it is generated from the crude palm oil process as a by-product. As the whole fruit bunch undergoes the steaming process in the palm oil mill, EFB is normally in a wet condition with very high moisture content. If it is not processed immediately, EFB is prone to degradation, which affects the quality of the fiber. Basically, EFB consists of cellulose, hemicellulose, and lignin. EFB fibers are partially separated by shredding the bunches. Some of the palm oil mills double shred the bunch and send it out to their plantations as mulching material. However, many of the mills just pile it at the plantation, letting it degrade slowly to create organic stockpile for the soil. Despite utilizing EFB for this low-end usage, EFB fiber has the potential to produce higher end products and has been recognized as an important lignocellulosic biomass. Due to its abundant availability in Malaysia, it is potentially considered as the main candidate as a substitute for wood and to assist in dealing with wood shortage problems.